2020
DOI: 10.1001/jamaoncol.2019.4320
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Breast-Conserving Surgery and 3-Dimensional Conformal Partial Breast Reirradiation for Recurrence of Breast Cancer in the Ipsilateral Breast

Abstract: IMPORTANCE Mastectomy is standard for recurrence of breast cancer after breast conservation therapy with whole breast irradiation. The emergence of partial breast irradiation led to consideration of its application for reirradiation after a second lumpectomy for treatment of recurrence of breast cancer in the ipsilateral breast.OBJECTIVES To assess the effectiveness and adverse effects of partial breast reirradiation after a second lumpectomy and whether the treatment is an acceptable alternative to mastectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 33 publications
0
45
0
1
Order By: Relevance
“…[ 32 ] 2019 50 12.7 Proton 45–76 97 16 Arthur DW et al. [ 33 ] 2019 58 66 3D CRT 45 1.5 BID 5.2 95 7 # pts: number of patients; MFU: median follow-up; Dose/f: dose per fraction; 3 rd IBTE: third ipsilateral breast tumor event rate; OS: overall survival; ≥ G3 tox. : grade 3 and higher toxicity rate; 3DCRT: 3D conformal radiation therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 32 ] 2019 50 12.7 Proton 45–76 97 16 Arthur DW et al. [ 33 ] 2019 58 66 3D CRT 45 1.5 BID 5.2 95 7 # pts: number of patients; MFU: median follow-up; Dose/f: dose per fraction; 3 rd IBTE: third ipsilateral breast tumor event rate; OS: overall survival; ≥ G3 tox. : grade 3 and higher toxicity rate; 3DCRT: 3D conformal radiation therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Re-irradiation of the regional nodes was done in 84% of the cases [ 32 ]. The results of the RTOG 10–14 phase 2 trial have been recently published with a MFU of 5.5 years [ 33 ]. With 4 pts out of 58 who developed a 3 rd IBTE, the authors reported a 3 rd IBTE 5-year cumulative incidence of 5% with an OS rate of 95%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes after second BCS and partial breast re-irradiation is a very current topic in the literature [22,23]. Recently, a study by Arthur et al demonstrates the long-term safety of this procedure, emphasizing the results of the GEC-ESTRO trial [24,25]. Since there are comparatively few long-term QoL studies in IBTR, we focused particularly on this item in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who undergo a second lumpectomy (for local recurrence or new primaries), a reasonable option is partial breast reirradiation, based on the recent RTOG 1014 that found DFS and OS to be 95% at 5 years. 17 "For patients who are very motivated to keep their breasts, this can be an effective alternative to mastectomy," she commented.…”
Section: Rt After Neoadjuvant Therapymentioning
confidence: 99%